Design of respirable sprayed microparticles of encapsulated bacteriophages - Baldelli, Alberto; Liang, Mingtao (Frontiers in Drug Delivery, 2023)
Antibiotic resistance is exponentially increasing, and the number of deaths caused by bacterial infections is expected to surge. When dealing with the respiratory system, if antibiotics are inefficient, the chance of death from bacterial infection is higher. The alternatives to antibiotics are limited. Bacteriophages are a valid option since they can target a specific type of bacterium. Bacteriophages are highly specific and can avoid any side effects when delivered. However, the poor stability of bacteriophages makes their use inefficient. Encapsulating is commonly used to protect any bioactive compound for different types of delivery. In the case of respiratory delivery, particle engineering is used to generate stable dry powders aiming to target the nasal or lung areas. This review article provides a guideline for the engineering process of nasal dry powders of encapsulated bacteriophages.